The new ageless ageing the natural way to stay young - Kenton, Leslie (Vermilion, 1995)
he New Ageless Ageing offers the ideal anti-ageing programme for the 21st century - a lifestyle that will prevent premature ageing, prolong vitality and good looks, and encourage longevity